Anastrozole Aromatase Inhibitor Plasma Drug Concentration Genome‐Wide Association Study: Functional Epistatic Interaction Between SLC38A7 and ALPPL2. Issue 1 (18th March 2019) - Dudenkov, Tanda M.; Liu, Duan; Cairns, Junmei; Devarajan, Sandhya; Zhuang, Yongxian; Ingle, James N.; Buzdar, Aman U.; Robson, Mark E.; Kubo, Michiaki; Batzler, Anthony; Barman, Poulami; Jenkins, Gregory D.; et al.
Abstract : Anastrozole is a widely prescribed aromatase inhibitor for the therapy of estrogen receptor positive (ER+) breast cancer. We performed a genome‐wide association study (GWAS) for plasma anastrozole concentrations in 687 postmenopausal women with ER+ breast cancer. The top single‐nucleotide polymorphism (SNP) signal mapped across SLC38A7 (rs11648166, P  =   2.3E‐08), which we showed to encode an anastrozole influx transporter. The second most significant signal (rs28845026, P  =   5.4E‐08) mapped near ALPPL2 and displayed epistasis with the SLC38A7 signal. Both of these SNPs were cis expression quantitative trait loci (eQTL)s for these genes, and patients homozygous for variant genotypes for both SNPs had the highest drug concentrations, the highest SLC38A7 expression, and the lowest ALPPL2 expression. In summary, our GWAS identified a novel gene encoding an anastrozole transporter, SLC38A7, as well as epistatic interaction between SNPs in that gene and SNPs near ALPPL2 that influenced both the expression of the transporter and anastrozole plasma concentrations.